Efficacy and safety of narrowband ultraviolet B therapy in moderate to severe atopic dermatitis - Nabi, Haroon; Din, Syed Shams-ud-; Asad, Faria; Nadeem, Muhammad (Journal of Pakistan Association of Dermatologists, 2016)
Background Atopic dermatitis is an inflammatory skin disorder with a chronic relapsing course. In troublesome cases of moderate and severe atopic dermatitis, phototherapy can be an effective treatment modality Objective To evaluate the efficacy and safety of narrowband UVB 311nm as a monotherapy in patients with moderate to severe atopic dermatitis. Patients and methods Patients suffering from moderate to severe atopic dermatitis, diagnosed according to criteria described by Hanifin and Rajka between ages of 6-70 were enrolled in the study. Severity of the disease was assessed by using SCORAD score. UVB irradiation was done thrice a week on alternate days. Efficacy was assessed every two weeks by reduction in modified SCORAD score. Results The mean cumulative dose of 25.91 J/cm2 UVB at a wavelength of 311nm was given in a mean of duration 5.2 weeks treatment. Therapy reduced the atopic dermatitis scores from mean 32.2 (range 20.2-45.5) to 14.2 range (6.2-12.4). Conclusion We conclude that narrowband UVB appears to be a promising treatment for AD, but large patient series, different dosing schedules and long- term safety considerations should be carefully evaluated in the future